Replication Initiation at a Distance: DETERMINATION OF THE CIS- AND TRANS-ACTING ELEMENTS OF REPLICATION ORIGIN α OF PLASMID R6K - Saxena, Mukesh (American Society for Biochemistry and Molecular Biology, 2010)
Plasmid R6K, which contains 3 replication origins called α, γ, and β, is a favorable system to investigate the molecular mechanism(s) of action at a distance, i.e. replication initiation at a considerable distance from the primary initiator protein binding sites (iterons). The centrally located γ origin contains 7 iterons that bind to the plasmid-encoded initiator protein, π. Ori α, located at a distance of ∼4 kb from γ, contains a single iteron that does not directly bind to π but is believed to access the protein by π-mediated α-γ iteron-iteron interaction that loops out the intervening ∼3.7 kb of DNA. Although the cis-acting components and the trans-acting proteins required for ori γ function have been analyzed in detail, such information was lacking for ori α. Here, we have identified both the sequence elements located at α and those at γ, that together promoted α activity. The data support the conclusion that besides the single iteron, a neighboring DNA primase recognition element called G site is essential for α-directed plasmid maintenance. Sequences preceding the iteron and immediately following the G site, although not absolutely necessary, appear to play a role in efficient plasmid maintenance. In addition, while both dnaA1 and dnaA2 boxes that bind to DnaA protein and are located at γ were essential for α activity, only dnaA2 was required for initiation at γ. Mutations in the AT-rich region of γ also abolished α function. These results are consistent with the interpretation that a protein-DNA complex consisting of π and DnaA forms at γ and activates α at a distance by DNA looping.